2012
DOI: 10.1016/j.anifeedsci.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of restricting enzyme supplementation in wheat-based diets to broilers

Abstract: The performance of broilers fed on xylanase supplemented diets for part or all of the production cycle was evaluated in two experiments. In a preliminary experiment, 1-day-old chicks were fed a wheat-based diet supplemented with a commercial xylanase for the entire duration of the experiment of 28 days, or during the last 21, 14, or 7 days of the trial. In experiment 2, the growth period was extended to 36 days, and birds were fed xylanase supplemented diets for the entire duration of the experiment, or during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Both diets contained small amounts of barley and rye, but we considered that these levels would not have a major effect on digestive physiology (Annison et al, 1996). Although all the diets, including the M, contained some amounts of NSP, there is a large amount of evidence that these levels allow gut productive performance and no evidence of nonspecific diarrhea (Figueiredo et al, 2012). We considered that there was no need to add any exogenous xylanases to the experimental diets.…”
Section: Diet Formulationmentioning
confidence: 99%
“…Both diets contained small amounts of barley and rye, but we considered that these levels would not have a major effect on digestive physiology (Annison et al, 1996). Although all the diets, including the M, contained some amounts of NSP, there is a large amount of evidence that these levels allow gut productive performance and no evidence of nonspecific diarrhea (Figueiredo et al, 2012). We considered that there was no need to add any exogenous xylanases to the experimental diets.…”
Section: Diet Formulationmentioning
confidence: 99%
“…Here, the improvement of BWG using XG compared to NC was more distinct in the grower than the starter period, especially using corn-SBM and corn/wheat-SBM. The appearance of performance effects of NSP degrading enzymes at later age, was also seen in another study [56] applying xylanase to a wheat-based diet. There, broiler BWG and F:G improved first at 21-28 d in comparison to the same diet without enzymes.…”
Section: Discussionmentioning
confidence: 73%
“…Shakaouri et al (2009) also reported that the addition of enzymes (Xylanase and β-glucanase) increases 28-day weight gain in broilers fed wheat-based diets but did not alter growth rates of birds offered Sorghum based diets. Figueiredo et al (2012) The lower feed intake of birds fed the control diet could be due to the presence of tannin. Studies has shown that tannin causes decrease feed consumption in animals; bind dietary protein and digestive enzymes to form complexes that are not readily digestible; decrease palatability and reduce growth rate (Habtamu and Nigussie, 2014).…”
Section: Growth Performance Of Broiler Chickens Fed Raw and Enzyme Tr...mentioning
confidence: 99%